PENGARUH KOMPETENSI DAN KARAKTERISTIK PEKERJAAN TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT MUJUR TIMBER SIBOLGA - Chindi Ellionora Tamba; Mansur Tanjung; Yacub Hutabarat (Universitas Sains dan Teknologi Komputer, 2022)
Productive employees are employees who are skilled and able to understand their work as expected and can be seen from the results of reports that are set to be completed in a shorter time, so that finally an effective and efficient level of employee productivity can be achieved. The formulation of the problem is the Influence of Competence and Job Characteristics on Employee Work Productivity at PT. Lucky Timber Sibolga. The objective of this research is to identify and analyze the effect of competence and job characteristics on employee productivity at PT. Lucky Timber Sibolga? the hypothesis in this study is that competence and job characteristics simultaneously influence the work productivity of employees at PT. Lucky Timber Sibolga. This type of research is descriptive correlational research. The population is 525 people and the sample in this study is 15% of (525 people), so that a total of 78 people are obtained. The results of the study found that competence and job characteristics can affect the work productivity variables of employees at PT. Lujur Timber Sibolga with 54.7%. Competence and job characteristics jointly affect the work productivity of employees at PT. Lucky Timber Sibolga. Where the Fcount value is greater than the Ftable value (45.363 > 3.11). Partially competence has a positive and significant effect on the work productivity of employees at PT. Lucky Timber Sibolga. Where the value of tcount = (2.515) > ttable (1.992), Partially the most dominant job characteristics affect employee work productivity, meaning that job characteristic variables are more decisive in increasing employee work productivity compared to competence. Where the value of tcount = (4.441) is greater than the value of ttable (1.992). The multiple linear regression equation Y = 9.965 + 0.250X1 + 0.582X2 employee productivity shows a positive direction. It is recommended to improve employee competence, it would be nice for the company to encourage employees to continue their education to the tertiary level or attend training held external to the company